Effectiveness of Using Animated Video Media Stories Prophet Ibrahim A.S. on Learning Motivation Students In Elementary School - Muhammad Nor Chudrin; Darnoto Darnoto (Eduvest - Journal of Universal Studies, 2024)
This research examines the effect of using animated media of the story of the prophet Ibrahim AS on students' learning motivation in elementary school. This study was conducted using a quantitative research type experimental. The research was conducted in one experimental class containing students with diverse academic abilities. The data collection technique used a wide pretest and posttest questionnaire. Data processing used a simple linear regression statistical data test carried out on the SPSS version 27 data application. Based on the results of the study, it was concluded that the use of animated video media had an effective influence on students' learning motivation in elementary school. The data test results showed a significance value of 0.000 <0.05, so Ho was accepted and Ha was rejected, so there was an effect influence in increasing students' learning motivation.